2010
DOI: 10.1002/adsc.200900900
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Aza‐Morita–Baylis–Hillman Reaction Using Aliphatic α‐Amidosulfones as Imine Surrogates

Abstract: The bifunctional catalyst 6'-deoxy-6'-acyl-A C H T U N G T R E N N U N G amino-b-isocupreidine (1) served both as a base to trigger the in situ generation of N-sulfonylimine from readily available a-amidosulfones and as a chiral nucleophile to initiate the enantioselective aza-Morita-Baylis-Hillman (aza-MBH) reaction. aMethylene-b-amino-b-alkyl carbonyl compounds, difficultly accessible previously, can now be synthesized in excellent yields and enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…[11] Indeed, the diverse reactivity of allenoates [10][11][12][13][14][15][16] and the complexity of the mechanism make the development of the asymmetric version particularly challenging. In connection with our ongoing project that deals with the catalytic potential of the cinchona-alkaloid-derived amides, [17][18][19] we became interested in examining the reaction of allenoates with imines in the presence of a chiral tertiary amine catalyst. Herein, we report the first examples of the catalytic enantioselective [2+2] cycloaddition between allenoates and N sulfonylimines to give enantioenriched 2alkylideneazetidines.…”
mentioning
confidence: 99%
“…[11] Indeed, the diverse reactivity of allenoates [10][11][12][13][14][15][16] and the complexity of the mechanism make the development of the asymmetric version particularly challenging. In connection with our ongoing project that deals with the catalytic potential of the cinchona-alkaloid-derived amides, [17][18][19] we became interested in examining the reaction of allenoates with imines in the presence of a chiral tertiary amine catalyst. Herein, we report the first examples of the catalytic enantioselective [2+2] cycloaddition between allenoates and N sulfonylimines to give enantioenriched 2alkylideneazetidines.…”
mentioning
confidence: 99%
“…Even though this is a well‐known reaction, only a few examples in the asymmetric field have been reported and most of these are related to the use of non‐substituted double bonds and ketones and esters as EWGs. Since the pioneering asymmetric aza‐Baylis–Hillman reaction published by Shi and co‐workers using tosylimines, excellent and brilliant asymmetric organocatalyzed examples have been shown by Masson and Zhu, Hatakeyama, Sasai,, and Jacobsen,, as well as asymmetric metal catalysis reported in the works of Shibata and Shibasaki, amongst others ,. All these examples have shown that the reaction can only take place with non‐substituted double bonds and mostly with ketone and esters (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…This reaction tendency is the same as that observed for β-ICD-catalyzed reactions. 7,8) To demonstrate the utility of α-ICPN, we examined aza-MBH reactions of aromatic imines 12 with β-naphthyl acrylate (13) employing catalyst 14 27) derived from α-ICPN and β-naphthol under the dual catalysis conditions developed by Masson and colleagues [28][29][30] As summarized in Chart 6, the reactions of 12 and 13 produced aza-MBH adducts 15 with high R-selectivity in the range of 80% ee to 96% ee, which is opposite to that observed in the reactions catalyzed by the corresponding β-ICD-derived catalyst. 28) The observed R-selectivity can be explained by assuming zwitterionic intermediates 16 28) stabilized by hydrogen bonding, from which a six-membered proton transfer followed by E1cb elimination of the catalyst takes place to give R-aza-MBH product 15.…”
Section: Asymmetric Morita-baylis-hillman Reactionmentioning
confidence: 99%